Endogenous Enforcement of Intellectual Property, North-South Trade, and Growth - Andreas Schäfer; Maik T. Schneider (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
While most countries have harmonized intellectual property rights (IPR) legislation, the dispute about the optimal level of IPR-enforcement remains. This paper develops an endogenous growth framework with two open economies satisfying the classical North-South assumptions to study (a) IPR-enforcement in a decentralized game and (b) the desired globally-harmonized IPR-enforcement of the two regions. The results are compared to the constrained-efficient enforcement level. Our main insights are: The regions' desired harmonized enforcement levels are higher than their equilibrium choices, however, the gap between the two shrinks with relative market size. While growth rates substiantially increase when IPR-enforcement is harmonized at the North's desired level, our numerical simulation suggests that the South may also benefit in terms of long-run welfare.
Keywords: F10; F13; O10; O30; 330; Endogenous Growth; Intellectual Property Rights; Trade; Dynamic Game; Immaterialgüterrechte; Rechtsdurchsetzung; Nord-Süd-Beziehungen; Spieltheorie; Endogenes Wachstumsmodell; Wohlfahrtsanalyse; Theorie